Effect of Environmental Cost on Financial Performance of Listed Construction and Real Estate Companies in Nigeria - Wokeh, Promise Ikechi (Research Parks Publishers, 2022)
This study examined the effect of environmental cost on financial performance of listed construction and real estate companies in Nigeria. The ex post facto research design was adopted for the study with a population of six (6) listed construction and real estate companies in Nigeria as listed by the Nigerian Exchange Group in 2022. Data were retrieved from the annual reports of the selected construction and real estate companies for the period 2017 to 2021. Multiple regression analysis was used to analysed the data gathered with the aid of Stata12 statistical software. The study revealed a positive and significant effect of employee health and safety cost on return on assets. Also, it revealed a positive and significant effect of donations and corporate social responsibility cost on return on assets. The study recommended that more measure should be put in place by regulatory bodies to ensure that listed construction and real estate companies in Nigeria are environmentally friendly in their operation and make full disclosure. Finally, management should establish clear lines of responsibility on environmental matters and give a board member overall responsibility for such issues.